Enzymes immobilized in mesoporous silica: A physical–chemical perspective - Carlsson, Nils; Gustafsson, Hanna; Thörn, Christian; Olsson, Lisbeth; Holmberg, Krister; Åkerman, Björn (Advances in colloid and interface science, 2014)
Mesoporous materials as support for immobilized enzymes have been explored extensively during the last two decades, primarily not only for biocatalysis applications, but also for biosensing, biofuels and enzyme-controlled drug delivery. The activity of the immobilized enzymes inside the pores is often different compared to that of the free enzymes, and an important challenge is to understand how the immobilization affects the enzymes in order to design immobilization conditions that lead to optimal enzyme activity. This review summarizes methods that can be used to understand how material properties can be linked to changes in enzyme activity. Real-time monitoring of the immobilization process and techniques that demonstrate that the enzymes are located inside the pores is discussed by contrasting them to the common practice of indirectly measuring the depletion of the protein concentration or enzyme activity in the surrounding bulk phase. We propose that pore filling (pore volume fraction occupied by proteins) is the best standard for comparing the amount of immobilized enzymes at the molecular level, and present equations to calculate pore filling from the more commonly reported immobilized mass. Methods to detect changes in enzyme structure upon immobilization and to study the microenvironment inside the pores are discussed in detail. Combining the knowledge generated from these methodologies should aid in rationally designing biocatalyst based on enzymes immobilized in mesoporous materials. [Display omitted] •Calculating pore filling as standard for comparing different mesoporous particles•Techniques for real time study of the immobilization process•Visualization of enzymes in the pores by microscopy•Methods for studying conformational changes of enzymes•Study of the microenvironment inside the pores as a function of material properties